The flight activity and infectivity of the major leafhopper vectors (Hemiptera: Cicadellidae) of rice tungro viruses in an irrigated rice area in the Philippines - Chancellor, T. C. B.; Cook, A.G.; Heong, K.L.; Villareal, S. (Cambridge University Press, 1997)
The flight activity of each of the three major leafhopper vectors of rice tungro viruses, Nephotettix virescens (Distant), N. nigropictus (Stål) and Recilia dorsalis (Motschulsky) was closely associated with rice cropping periods and was influenced by crop growth stage and season. Leafhopper flight was influenced by changing levels of illumination at dusk and dawn and, for R. dorsalis only, was significantly affected by moon phase. Recilia dorsalis was the dominant species caught in suction traps at 0.75 m and 1.5 m and an upwardly-directed light trap at 4.0 m, whereas N. virescens was the most abundant species caught on sticky yellow traps at the height of the canopy. Infectivity tests on migrant leafhoppers caught in upwardly-directed light traps showed that N. virescens was the most common transmitter of rice tungro viruses. Infective leafhoppers were recorded at the end of dry seasons and during wet seasons in 1991 and 1992. The risk of tungro disease incidence was very low early in the 1991 dry season, when aerial abundance of leafhoppers was small and no infective individuals were recorded.